Financing of Non-Communicable Diseases Prevention in Low- and Middle- Income Countries: Mongolia Case Study - Ammar Rashid; Kassim Nishtar; Saba Amjad; Anum Siddiqui (Journal of the Pakistan Medical Association, 2026)
Objective: Prevention programmes are increasingly seen as critical for tackling the rising burden of noncommunicable diseases (NCDs), but tend to be under-prioritised and under-funded, particularly in low- and middleincome countries. The objective of this study is to estimate spending on NCD prevention in Mongolia and identify the enablers, challenges and dynamics underpinning population-level NCD prevention spending, with particular focus on tobacco use, harmful use of alcohol, unhealthy diets and physical inactivity. Methods: Primary and secondary data collection was used to examine processes and organisational contexts that shape the formulation of policy and financial frameworks for NCD prevention. The methodology was categorised into three tiers; an academic literature review, scrutiny and analysis of official policy documents and budgetary data on health and NCDs, and in-depth stakeholder interviews with key government officials leading NCD programmes. Government and government-routed donor spending on population level prevention was gauged to estimate NCD prevention spending. Where possible, impact of prevention programmes on disease incidence and risk factors was gauged through available outcome indicators. Results: Mongolia allocated an estimated MNT 10.5 billion on NCD prevention and health promotion in 2017, out of which population-level NCD spending accounted for MNT 5.1 billion (just over 1% of overall government health spending). Enablers include tobacco taxation and regulation, earmarking unhealthy consumption through the Health Promotion Fund and strengthened salt intake policies. Challenges include excess allocations towards inpatient and specialist care, inadequate multi-sectoral action and stewardship for NCDs, food and beverage industry interference in policy and limited alcohol regulation and tax. Conclusion: Mongolia has made considerable progress in formulating policies for NCD prevention, but spending on NCD prevention still remains barely more than 1% of government health spending. Increased allocation of resources towards population-level NCD prevention can both help address the growing NCD burden and bring substantial economic benefits. Keywords: Noncommunicable Diseases, Tobacco, Sodium Chloride, Dietary, Employees, Incidence, Inpatients, Behaviour, Risk Factors, Diet, Resource, Tobacco, Beverages, Taxes, Financial Management